Prevalencia de coccidios y microsporidios intestinales en una comunidad indígena del estado Zulia, Venezuela - Rivero Zulbey; Bracho Angela; Huerta Karen; González Jorelys; Uribe Ismael (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2013)
Abstract: In order to determine the prevalence of intestinal coccidia and microsporidia, fecal samples from individuals of an indigenous community in Perijá, State of Zulia, Venezuela, were studied. One-hundred seventy-two (172) fecal samples from people of both genders between 1 month and 86 years of age were subjected to macroscopic and microscopic examination with physiological saline, Lugol and formalin-ether concentration. Only 145 underwent Kinyoun and gram-chromotrope stains. The following species were identified: Cystoisospora belli in 3 individuals (2.07%); Cryptosporidium spp. in 2 cases (1.38%); Cyclospora cayetanensis in 1 case (0.69%); and microsporidia spores in 5 people (3.45%). Most of those infected with coccidia and intestinal microsporidia (9/11) had associations with other parasitic species, mainly protozoa. A high percentage (54.54%) of the coccidian and microsporidia carriers provided samples of diarrheal and liquid consistency with mucus and were persons included in risk groups (children and elderly). Results emphasize the need for diagnosis by special stains for intestinal coccidia and microsporidia, even in immunocompetent and low-risk individuals, such as the indigenous studied. Resumen: Con la finalidad de determinar la prevalencia de coccidios y microsporidios intestinales, se estudiaron las muestras fecales de individuos de una comunidad indígena de la Sierra de Perijá, Estado Zulia, Venezuela. Para ello, se recolectaron 172 muestras fecales de personas de ambos géneros, con edades comprendidas entre 1 mes y 86 años, a las cuales se les realizaron examen macroscópico y microscópico con solución salina fisiológica, lugol y concentración por formol-éter; del total de muestras solo 145 fueron sometidas a las coloraciones de Kinyoun y Gram-Cromotropo. Dentro de las especies encontradas, se identificó en 3 individuos (2,07%) Cystoisospora belli, Cryptosporidium spp. en 2 (1,38%), Cyclospora cayetanensis en 1 (0,69%) y esporas de Microsporidios en 5 personas (3,45%). La mayoría de los infectados con coccidios y microsporidios intestinales (9/11) presentó asociaciones con otras especies parasitarias, principalmente protozoarios. Un alto porcentaje (54,54%) de los portadores de coccidios y microsporidios, presentó muestras de consistencia diarreica o liquida con moco; tratándose además de personas incluidas en grupos de riesgo (niños y ancianos). Se resalta la necesidad de efectuar el diagnóstico mediante coloraciones especiales para coccidios y microsporidios intestinales, aún en individuos inmunocompetentes y de bajo riesgo, como los indígenas estudiados.